(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: The Supreme Court of India decreed that a physician owes a duty of care towards his patients while deciding whether or not to embark on the case and a duty of care in deciding the mode of administration and modality of the proposed treatment plan. Any breach of duty would make him liable for a cause of action against him. Materials and methods: A total of 89 cases within a 2½ year period were studied with the aim of analysing the pattern of cases of medical negligence filed in the State Commissions of Northern India; reasons for filing them, outcome of the suits and the time frame of decision making process. Results: Doctors belonging to single specialty (in comparison to composite negligence) were implicated in 82% cases and General Surgery was at the highest risk of litigation, with 16.5% cases, followed by Gynaecology, 11%. Most of the litigants were male and from urban areas. Maximum cases were filed against self-owned establishments, while govt. hospitals were the most immune.